SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI INDONESIA - Dhafa Purbaya Nurrohim; Bambang Eko Susilo (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study was motivated by the low level of students’ mathematical critical thinking skills in Indonesia, indicating the need for learning models that can increase students’ active participation in mathematics learning. This study aims to analyze the effectiveness of the jigsaw cooperative learning model in improving students’ mathematical critical thinking skills in Indonesia and to identify the characteristics of previous studies based on educational level, research method, learning media, learning materials, and regional distribution. The method used in this study was a Systematic Literature Review (SLR) by analyzing 15 scientific articles indexed in SINTA and Scopus published between 2016 and 2025 that met the inclusion criteria. The data were analyzed descriptively and thematically based on the research questions. The results showed that the jigsaw cooperative learning model was effective in improving students’ mathematical critical thinking skills through discussion activities, group collaboration, and active student involvement in the learning process. In addition, the reviewed studies were dominated by quantitative approaches, elementary school level, and the use of printed learning media. Therefore, the jigsaw cooperative learning model can serve as an effective and relevant alternative learning model for improving students’ mathematical critical thinking skills.